Chemical components of boiling-treated sengon (Paraserianthes falcataria (L.) I. C. Nielsen) wood - Fajar Arief Kurniawan; Audyta Aurelia Syaharanie; Ganis Lukmandaru (Wood Research Journal, 2024)
Sengon is a fast-growing wood species widely distributed on Java Island and commonly utilised for plywood production. It is frequently subjected to boiling treatment to reduce veneer defects, making it important to understand how this treatment affects its properties. This study investigated the effect of boiling treatment on the properties of sengon wood, involving three seven-year-old trees which were subjected to a control and an experimental treatment at 80℃ for ten hours. The wood specimens were divided into near-pith, middle, and near-bark sections. The specimens were powdered to a size of 40–60 mesh for successive extraction with n-hexane, methanol, and hot water. The total phenolic content was measured from the methanol-soluble extract, and the total polysaccharide content was measured from the hot-water-soluble extract. Chemical components such as holocellulose, alpha-cellulose, hemicellulose, lignin, ash, and silica contents, as well as pH values, were determined. T-test revealed that boiling treatment significantly reduced extractive levels (in ethanol-toluene and methanol solubles) but significantly increased total phenolic and polysaccharide contents. No significant effect was observed on cell wall chemical components. One-way ANOVA indicated that the radial direction significantly affected methanol-soluble extractive content, total phenolic content, and total polysaccharide content.